The importance of teacher interpersonal communication as an effort to maintain students' mental health: a study of lerature review - Eli Sabrifha; Darmawati Darmawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Mental health disorders in students have increased significantly in recent years, including anxiety, depression, stress, and feelings of isolation. Teachers have an important role not only as information transmitters but also as effective learning facilitators. Empirical and responsive interpersonal communication can provide the support, understanding, and guidance needed to maintain students' mental health. The purpose of this article is to provide an overview of the role of interpersonal communication in maintaining students' mental health. This article aims to inform readers of the role teachers play in supporting students' mental health through good interpersonal communication. The method used is a review of the literature by taking an article that can answer research problems. In this case, there are four main sources for research references. The result of this study is that teachers need to establish good interpersonal communication with students to support their mental health. Empirical, responsive, and inclusive communication can provide the support, understanding, and guidance needed to address academic anxiety, depression, stress, feelings of isolation, low self-esteem, and emotional problems. Positive emotional relationships between teachers and students create a safe, supportive, and mental well-being environment for students. Teacher interpersonal communication also promotes collaborative communication between teachers and students. Active participation and open discussion help students feel involved in the learning process, build confidence, and pay attention to their emotional needs. To improve teachers' interpersonal communication, educational institutions need to provide appropriate training and support. Teachers need to develop effective communication skills and an understanding of students' mental health. A supportive and stigma-free environment must also be created so that students feel comfortable talking about health issues.